Neuronal effects of epicranial current stimulation in macaque cortex - Asamoah, Boateng; Khatoun, Ahmad; Romero, Maria C.; Premereur, Elsie; Janssen, Peter; Mc Laughlin, Myles (Frontiers in Neuroscience, 2025)
BackgroundTranscranial electrical stimulation (TES) using scalp electrodes is noninvasive, safe and inexpensive. However, because the scalp shunts most of the current, electric fields (E-fields) in the brain are relatively weak. Conversely, invasive neuromodulation methods such as deep brain stimulation (DBS) and invasive cortical stimulation (ICS) successfully treat many brain diseases. However, the expensive and risky surgery limits the reach of these approaches. Epicranial current stimulation (ECS), where electrodes are implanted on the skull, is a novel approach which can bridge the gap between these two extremes. In current study we investigated the effects of ECS on neural activity.MethodsIn two macaque monkeys we implanted two concentric ring electrodes directly on the skull. Each electrode targeted one area PFG (PFG is not an acronym; rather it is the full name of a particular part of the parietal cortex) of the parietal convexity. Furthermore, a craniotomy was drilled in the skull to access the same area PFG. While recording (2 min) we stimulated (during the second recording minute) with a 10 or 40 Hz sinewave using an unfocused montage (between two electrodes on each side of the head) or a focused (through the concentric electrodes) over an intensity range of 0.25 to 4 mA. These two montages allowed us to investigate neural responses to targeted and broad brain stimulation. Furthermore, in a functional magnetic resonance imaging (fMRI) experiment we stimulated, at only 10 Hz, through an unfocused montage.ResultsOur results show that E-field strengths depended on a combination of montage and stimulation intensity. Depending on the montage stimulation caused entrainment as well as spike rate increases. For focused stimulation and unfocused stimulation at lower amplitudes neural activity became entrained to the stimulation (similar to TES). For the unfocused stimulation, as stimulation amplitude increased, spike-rates also increased (similar to ICS and DBS) while the unfocused did not affect spike rates. The fMRI study showed a distributed pattern of activations which is suggestive of a network response caused by ECS.ConclusionECS has been used as a proxy for transcutaneous stimulation in rodent setups. Here we show that as a standalone technique it can be applied to a larger and more complex brain. This makes it a promising neuromodulation approach with clinical applications in patients who do not respond to TES but are not yet candidates for ICS or DBS.